Epidemiology of multimorbidity in conditions of extreme poverty: a population-based study of older adults in rural Burkina Faso - Guy Harling; Justine I Davies; Till Bärnighausen; Miles D Witham; Mark J Siedner; Jennifer Manne-Goehler; Pascal Geldsetzer; Ali Sie; Lucienne Ouermi; Collin Payne; Mamadou Bountogo; Boubacar Coulibaly; et al. (BMJ Global Health)
Introduction Multimorbidity is a health issue of increasing importance worldwide, and is likely to become particularly problematic in low-income countries (LICs) as they undergo economic, demographic and epidemiological transitions. Knowledge of the burden and consequences of multimorbidity in LICs is needed to inform appropriate interventions.Methods A cross-sectional household survey collected data on morbidities and frailty, disability, quality of life and physical performance on individuals aged over 40 years of age living in the Nouna Health and Demographic Surveillance System area in northwestern Burkina Faso. We defined multimorbidity as the occurrence of two or more conditions, and evaluated the prevalence of and whether this was concordant (conditions in the same morbidity domain of communicable, non-communicable diseases (NCDs) or mental health (MH)) or discordant (conditions in different morbidity domains) multimorbidity. Finally, we fitted multivariable regression models to determine associated factors and consequences of multimorbidity.Results Multimorbidity was present in 22.8 (95% CI, 21.4 to 24.2) of the study population; it was more common in females, those who are older, single, more educated, and wealthier. We found a similar prevalence of discordant 11.1 (95% CI, 10.1 to 12.2) and concordant multimorbidity 11.7 (95% CI, 10.6 to 12.8). After controlling for age, sex, marital status, education, and wealth, an increasing number of conditions was strongly associated with frailty, disability, low quality of life, and poor physical performance. We found no difference in the association between concordant and discordant multimorbidity and outcomes, however people who were multimorbid with NCDs alone had better outcomes than those with multimorbidity with NCDs and MH disorders or MH multimorbidity alone.Conclusions Multimorbidity is prevalent in this poor, rural population and is associated with markers of decreased physical performance and quality of life. Preventative and management interventions are needed to ensure that health systems can deal with increasing multimorbidity and its downstream consequences.